Watershed conservation prioritization using geomorphometric and land use-land cover parameters - G.R. Puno; R.C.C. Puno (Global Journal of Environmental Science and Management)
Geomorphometric features and land use/land cover are essential in the context of watershed prioritization for resources conservation and protection. Watersheds in tropical regions like the Philippines are under threat of degradation due to the combined effects of uncontrolled agricultural activities in the uplands and frequently increasing erosive precipitations brought about by climate change. Watershed managers are challenged with these pressing issues and concerns because most watersheds have no sufficient data as a basis for decision making. This paper presents the method of analyzing the different geomorphometric features and the existing land use or land cover to assess the propensity of the watershed against erosion so that areas needing immediate treatment can be prioritized. Arbitrarily, fourteen subwatersheds coded as SW1 to SW14 were delineated using a digital elevation model and geographic information system tool. Geomorphometric features categorized as areal aspect, relief features, and channel morphology parameters were generated and analyzed. Parameters having direct and inverse effect to erosion risk was used as the criteria in the ranking process. Land use/land cover was added to geomorphometric parameters to come up with compound values for final prioritization. Results showed that SW13, SW14, and SW4 were classified under very high priority implying focus for appropriate management actions while SW10, SW6, and SW7 were classified under very low priority suggesting favorable environmental condition in these areas. The study provides significant information helpful to watershed managers and planners especially in crafting a plan for integrated watershed management wherein programs and projects implementation have to be prioritized.